60-minute CEO : Mastering leadership an HOUR at a time - Cross, Dick
Looking toward the C-suite? Take heed. Author and serial CEO Dick Cross pulls back the curtain on this top leadership role, explaining in his new book that being a successful leader, running a business, and doing it extraordinarily well isn't a full-tim